Nuclear terrorism: what can we learn from South Africa's development of nuclear devices?. Issue 2 (4th May 2019) - Volders, Brecht
ABSTRACT: Traditional assessments of nuclear terrorism threats primarily focus on the motivation of terrorist organizations to go nuclear, the availability of know-how, and the opportunities to obtain fissile material. The organizational challenges of implementing the construction and detonation of an improvised nuclear device are not often systematically explored. To contribute to a more comprehensive understanding of the threat, this article aims to study South Africa's Peaceful Nuclear Explosives programme to verify and further refine the idea of an effectiveness-efficiency trade-off for terrorist organizations pursuing a nuclear terrorism plot.